The maintenance system for a smart building in industry 4.0 environment - Mossa, Muntasser A. A.; Tang, Sai Hong; Alrifaey, Moath; Thum, Guan Wei (Suranaree University of Technology, 2023)
Buildings, where we spend the majority of our time, have been quickly altering in recent years. Building systems powering integrate consumer-grade Internet of things (IoT) sensors such as cameras with operational technology controllers and actuators to accommodate the increased complexity of building operations. This study discussed the idea of “smart buildings” and the comparison along with the technologies being developed for these structures and the implications for libraries and specialized smart building technology using various IoT approaches used in smart building categories. The research goal is to improve approaches which active in recent years and the gaps researchers have found in their investigations. As a result, smart buildings provide physical value by generating data intelligently to enhance operations and customer skills. Recent breakthroughs in IoT have piqued experts and engineers across the world. However, improvements are only possible if we consider the numerous flaws and mistakes in the present technology. IoT developers might consider many challenges and hurdles while designing a better model in this survey article. Significant IoT technology sectors in which IoT developers and academics are interested are frequently addressed. In addition to providing services, IoT captures a vast amount of data. Therefore, big data analytics is essential, trustworthy judgments can be made, and a more robust IoT framework can be created.  This study compares the previous studies that focused on characteristics that a controlling and advanced approach to making buildings smarter with Maintenance to reduce greenhouse gas emissions and enhance the world's environment at a lower cost.